2016
DOI: 10.3389/fpsyg.2016.00467
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms and Associated Psychosocial Factors among Adolescent Survivors 30 Months after 2008 Wenchuan Earthquake: A Follow-Up Study

Abstract: Purpose: This study longitudinally investigated the changes of depressive symptoms among adolescent survivors over 2 years and a half after the 2008 Wenchuan earthquake in China, as well as the predictive effects of demographic characteristics, earthquake exposure, negative life events, social support, and dispositional resilience on the risk of depressive symptoms at two time points after the earthquake.Methods: Participants were 1573 adolescent survivors (720 males and 853 females, mean age at initial survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 45 publications
3
17
1
2
Order By: Relevance
“…Firstly, we assessed the prevalence of depression in this study, and found that the prevalence was 62.8% among adolescents 18 months after the Wenchuan earthquake, higher than that (e.g., 27.6, 40.6, 30.9, 37.5, and 29.8% after 6, 12, 18, 24, and 30 months since earthquake) found in the studies from Fan’s team (e.g., Shi et al, 2016; Zhou et al, 2016). The difference can be attributed to the different participants.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Firstly, we assessed the prevalence of depression in this study, and found that the prevalence was 62.8% among adolescents 18 months after the Wenchuan earthquake, higher than that (e.g., 27.6, 40.6, 30.9, 37.5, and 29.8% after 6, 12, 18, 24, and 30 months since earthquake) found in the studies from Fan’s team (e.g., Shi et al, 2016; Zhou et al, 2016). The difference can be attributed to the different participants.…”
Section: Discussionmentioning
confidence: 68%
“…The difference can be attributed to the different participants. Specifically, the adolescents Fan’s team investigated were from Dujiangyan city, about 20 kms away from the epicenter (e.g., Shi et al, 2016; Zhou et al, 2016). However, the Wenchuan and Maoxian county, where the adolescents in the current study came from, are the epicenter.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of items in the RS-14 include: "When I'm in a difficult situation, I can usually find my way out of it, " "My belief in myself gets me through hard times, " and "I am determined." RS-14 shows both cross-ethnic validity in the United States and good reliability amongst Chinese adolescents (Pritzker and Minter, 2014;Shi et al, 2016). For this study the Cronbach's alpha was 0.90.…”
Section: Methodsmentioning
confidence: 75%
“…RS‐14 assesses resilience‐related traits, which involve a set of personal characteristics that can mediate the impact of adverse life conditions on psychological adjustment (Wagnild, ; Wagnild & Young, ). Examples of items include “I am determined;” “My belief in myself gets me through hard times;” and “When I'm in a difficult situation, I can usually find my way out of it.” The scale has demonstrated cross‐ethnic validity in the United States and good reliability among adolescents in China (Pritzker & Minter, ; Shi, Yu, Zhou, Geng, & Fan, ). The Cronbach's alpha of these items was 0.87 for this study.…”
Section: Methodsmentioning
confidence: 99%